Determining Secondary School Students’ Knowledge and Awareness about Antarctica - Nazihan Ursavas; Raif Kandemir (Universitas Pendidikan Indonesia, 2020)
Antarctica has been an object of interest for a long. It is considered important to increase individuals awareness and knowledge about Antarctica. The accuracy of individuals’ scientific knowledge plays an important role in creating the awareness. In this study, the 349 secondary school students’ knowledge and awareness about Antarctica was determined quantitatively with a questionnaire. Nineteen questions, including current topics were prepared. that addressed from biological geographic and climatic perspectives. According to the findings, 40% of the students thought Antarctica is in the North Pole, 42.6% thought polar bears and penguins live together; 46.6% thought Antarctica is best visited during summer months, 70.5% thought most glaciers are located in the northern hemisphere. Based on these findings, it can be said that students have inadequate and alternative conceptions about Antarctica. Studies can be conducted to determine how best to increase students’ awareness.